Salat Tasbih, Sunnah atau Bid’ah? (Studi Atas Kualitas Hadith Salat Tasbih) - Gultom Harahap; Ahmad Khoirul Fata (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2021)
This research discusses the hadith about the Tasbih prayer. The researcher focuses on the quality of the sanad and the matan of the hadiths. Based on the researcher discussion, it concluded that although there were many narrations about the sunnah of the Tasbih prayer which have weaknesses in the narrators, but the hadiths related to it were valid to be used as evidence in terms of both the sanad and the matan. Among the narrations about the Tasbih prayer was the hadith of Ibn Abbas ra. from the path of Ikrimah ra. and the Hadith of Al-Anshary from the path of Urwan bin Ruawimi. The opinion, therefore, which permitted the prayer of tasbih circumcision to be carried out, was stronger than that which prohibited it. The argument about the Tasbih prayer, whether it was sunnah or not, was the foundation of this research.